Pharmacotherapy for alcohol dependence: the 2015 recommendations of the French Alcohol Society, issued in partnership with the European Federation of Addiction Societies - Rolland, Benjamin; Mann, Karl (CNS neuroscience & therapeutics, 2016)
Background The latest French good practice recommendations (GPRs) for the screening, prevention, and treatment of alcohol misuse were recently published in partnership with the European Federation of Addiction Societies (EUFAS). This article aims to synthesize the GPRs focused on the pharmacotherapy of alcohol dependence. Methods A four-member European steering committee defined the questions that were addressed to an 18-member multiprofessional working group (WG). The WG developed the GPRs based on a systematic, hierarchical, and structured literature search and submitted the document to two review processes involving 37 French members from multiple disciplines and 5 non-French EUFAS members. The final GPRs were graded A, B, or C, or expert consensus (EC) using a reference recommendation grading system. Results The treatment of alcohol dependence consists of either alcohol detoxification or abstinence maintenance programs or drinking reduction programs. The therapeutic objective is the result of a decision made jointly by the physician and the patient. For alcohol detoxification, benzodiazepines (BZDs) are recommended in first-line (grade A). BZD dosing should be guided by regular clinical monitoring (grade B). Residential detoxification is more appropriate for patients with a history of seizures, delirium tremens, unstable psychiatric comorbidity, or another associated substance use disorder (grade B). BZDs are only justified beyond a 1-week period in the case of persistent withdrawal symptoms, withdrawal events or associated BZD dependence (grade B). BZDs should not be continued for more than 4 weeks (grade C). The dosing and duration of thiamine (vitamin B1) during detoxification should be adapted to nutritional status (EC). For relapse prevention, acamprosate and naltrexone are recommended as first-line medications (grade A). Disulfiram can be proposed as second-line option in patients with sufficient information and supervision (EC). For reducing alcohol consumption, nalmefene is indicated in first line (grade A). The second-line prescription of baclofen, up to 300 mg/day, to prevent relapse or reduce drinking should be carried out according to the “temporary recommendation for use” measure issued by the French Health Agency (EC). During pregnancy, abstinence is recommended (EC). If alcohol detoxification is conducted during pregnancy, BZD use is recommended (grade B). No medication other than those for alcohol detoxification should be initiated in pregnant or breastfeeding women (EC). In a stabilized pregnant patient taking medication to support abstinence, the continuation of the drug should be considered on a case-by-case basis, weighing the benefit/risk ratio. Only disulfiram should be always stopped, given the unknown risks of the antabuse effect on the fetus (EC). First-line treatments to help maintain abstinence or reduce drinking are off-label for people under 18 years of age and should thus be considered on a case-by-case basis after the repeated failure of psychosocial measures alone (EC). Short half-life BZDs should be preferred for the detoxification of elderly patients (grade B). The initial doses of BZDs should be reduced by 30 to 50% in elderly patients (EC). In patients with chronic alcohol-related physical disorders, abstinence is recommended (EC). Any antidepressant or anxiolytic medication should be introduced after a psychiatric reassessment after 2-4 weeks of alcohol abstinence or low-risk use (grade B). A smoking cessation program should be offered to any smokers involved in an alcohol treatment program (grade B).